Tuning the Crystal Polymorphs of Alkyl Thienoacene via Solution Self‐Assembly Toward Air‐Stable and High‐Performance Organic Field‐Effect Transistors. (17th December 2014) - He, Ping; Tu, Zeyi; Zhao, Guangyao; Zhen, Yonggang; Geng, Hua; Yi, Yuanping; Wang, Zongrui; Zhang, Hantang; Xu, Chunhui; Liu, Jie; Lu, Xiuqiang; Fu, Xiaolong; et al.
<x xml:space="preserve">Abstract</x> The first example for thienoacene derivatives with selective growth of different crystal polymorphs is simply achieved by solution‐phase self‐assembly. Compared with platelet‐shaped α‐phase crystals, organic field‐effect transistors (OFETs) based on microribbon‐shaped β‐phase crystals show a hole mobility up to 18.9 cm2 V−1 s−1, which is one of the highest values for p‐type organic semiconductors measured under ambient conditions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>